La relation entre l’attitude envers la science et son enseignement en classe de personnes enseignantes au primaire et leur utilisation d’un organisme de promotion de la culture scientifique et technologique - Chastenay, Pierre; Marec, Claude-Émilie; Desjarlais, Estelle; Ayotte-Beaudet, Jean-Philippe; Rodrigue-Poulin, Élise; Skelling Desmeules, Yannick; Brouillard, Martin (Canadian Journal of Education/Revue canadienne de l'éducation, 2024)
The teaching of science and technology [ST] at the primary level suffers from a certain disengagement on the part of many teachers. A number of authors suggest that improving the teaching of ST at the primary level would require a more positive attitude toward ST and its teaching on the part of these teachers. One way of achieving this would be to have teachers supported by organizations promoting scientific and technological culture [OPSTC] “to stimulate student interest and support science and technology teachers” (Conseil supérieur de l’éducation, 2013, p. 74). However, little is known about the links between a primary school teacher’s attitude toward ST and the teaching of this subject in the classroom and his or her use of the services of an OPSTC. In this case study, we were therefore interested in these links, particularly among teachers who use the services of the OPSTC Les neurones atomiques [NA]. We began by quantitatively measuring the attitudes toward ST and its teaching of teachers using NA services (N = 206) using the “Dimensions of Attitude towards Science” (DAS) questionnaire. We then conducted semi-structured interviews with nine teachers presenting various attitude profiles toward ST and its teaching (positive attitude, positive attitude with context dependence, and reluctant attitude). Our results suggest a strong link between a teacher’s attitude toward ST and its teaching and the way in which he or she uses the services of an OPSTC such as the NA (preparatory and follow-up activities, participation during facilitation, etc.). We also note that teachers in all three attitude profiles invite the NA into their classrooms for similar reasons. We outline the advantages, but also the limitations, of this type of classroom intervention by an OPSTC on teachers’ appropriation of ST teaching, and propose ways in which OPSTC such as NAs can contribute to enhancing ST teaching at the primary level.